New developments in diagnosis, prognostication, and treatment of advanced systemic mastocytosis - Reiter, Andreas; George, Tracy I.; Gotlib, Jason (Blood, 2020)
Systemic mastocytosis (SM) has greatly benefited from the broad application of precision medicine techniques to hematolymphoid neoplasms. Sensitive detection of the recurrent KIT D816V mutation and use of next-generation sequencing (NGS) panels to profile the genetic landscape of SM variants have been critical adjuncts to the diagnosis and subclassification of SM, and development of clinical-molecular prognostic scoring systems. Multilineage KIT involvement and multimutated clones are characteristic of advanced SM (advSM), especially SM with an associated hematologic neoplasm (AHN). A major challenge is how to integrate conventional markers of mast cell disease burden (percentage of bone marrow mast cell infiltration and serum tryptase levels) with molecular data (serial monitoring of both KIT D816V variant allele frequency and NGS panels) to lend more diagnostic and prognostic clarity to the heterogeneous clinical presentations and natural histories of advSM. The approval of the multikinase/KIT inhibitor midostaurin has validated the paradigm of KIT inhibition in advSM, and the efficacy and safety of second-generation agents, such as the switch-control inhibitor ripretinib (DCC-2618) and the D816V-selective inhibitor avapritinib (BLU-285) are being further defined in ongoing clinical trials. Looking forward, perhaps the most fruitful marriage of the advances in molecular genetics and treatment will be the design of adaptive basket trials that combine histopathology and genetic profiling to individualize treatment approaches for patients with diverse AHNs and relapsed/refractory SM.
Gesehen am 06.07.2020